Export Restrictions on COVID-19 Vaccines: What Developing Countries Can Do Under the WTO Law? - Widiatedja, Ngurah Parikesit (UI Scholars Hub, 2022)
The COVID-19 pandemic has wreaked havoc on the global economy and trade, since production and consumption have been reduced around the world. The production and distribution of COVID-19 Vaccines caused unequal distribution as some developed countries have imposed export restrictions. As a result, wealthier countries are resuming normalcy, while the rest of the world continues to struggle to vaccinate its citizens. Article XI(2)(a) of The General Agreement on Tariffs and Trade exceptions allow members the legal ability to impose export restrictions if they meet specific criteria: they must be temporary, confined to foodstuffs and vital products, and enforced in the context of preventing and easing critical shortages. Export restrictions on COVID-19 vaccine applied by developed countries appear to meet these criteria, given that all of these countries are facing a shortage, and the restrictions are being placed to alleviate the shortage. Responding to this unpleasant measure, this article finds that developing countries may employ two available alternative measures, namely compulsory licensing and security exceptions under the Agreement on Trade-Related Aspects of Intellectual Property Rights to protest unequal distribution of the vaccine around the world.